Estrange conflict : fragments of the Irish Troubles in the science fiction of Bob Shaw and James White - Howard, Richard (Trinity College (Dublin, Ireland). School of English, 2016)
A study of the work of the Belfast science fiction authors Bob Shaw and James White, two hitherto ignored authors in Irish Studies. Much written about Shaw and White has originated from British and American science fiction fandom, but this project assesses their work against the background of the Northern Ireland in which their work was produced. The thesis takes a broadly Marxist approach, in particular utilising the Marxist approach to the science fiction genre developed by Fredric Jameson, Darko Suvin and Carl Freedman, as well as drawing from Irish Studies, Science and Technology Studies, Utopian Studies, and Postcolonial Studies. Chapter One sketches out the a priori conditions for the emergence of the science fiction form in Belfast, utilising historical texts, the work of Fredric Jameson on modernity, and also drawing from the discipline of Science and Technology Studies. It draws out the link between development and the science fiction of Shaw and White, pointing to the ideologeme of improvement through technology reflected in their work. The chapter also locates a connection between the de-industrialisation experienced by Belfast from the late 1970s onward, and the depiction of ragged technologies and alternative means of development in the later works of both authors.
Embargo End Date: 2023-07-01
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin, 2016